Flaming Badger and Snotnose: The Infantilization of Political Communication in Croatia - Tea Škokić; Ozren Biti ([sic])
This article delves into the analysis of political communication between two Croatian political leaders, Prime Minister Andrej Plenković and President Zoran Milanović, through the prism of the infantilization of politics as part of the broader context of the infantilization of society. To achieve this, the article introduces selected theoretical theses on the infantilization of society and on how the expression of infantile (political) disgust, as a speech act, contaminates and pollutes the community. By employing Critical Discourse Analysis, the paper aims to illustrate how, in the case of these two politicians, the infantilization of politics is characterized by the replacement of political discourse with personal insults, witticism, affectation, and emotions such as disgust, occasionally intertwined with elements of narcissism. Exploring how their political discourse tends to be personalized and even celebritized, the paper shows how it further contributes to the overall infantilization of society.